PERBEDAAN PENGARUH LAMA PENYIMPANAN LARUTAN SUSU BUBUK FULL CREAM DAN LARUTAN SUSU KENTAL MANIS TERHADAP KADAR GLUKOSA - Risha Fillah Fithria; Agus Suprijono; Maywan Hariono (Universitas Wahid Hasyim Semarang, 2012)
ABSTRACTMilk and the products which have expired usually be thrown by people immediately.However, those are still having lactose content even do not like as much as a fresh milk. Lactose content of milk and the expired products can be extracted and then hydrolized to yield glucose and galactose. The glucose content can be determined, so it will give information about ehancing value of expired milk that the glucose content can be developed furthermore to larger scale (industrial scale). This research was aimed to know influence of storage duration toward glucose content of fresh milk, full cream milk powder solution and sweet concentrate milk solution, and comparison of glucose content for each product. Research object was glucose content of fresh milk, full cream milk powder solution and sweet concentrate milk solution which was store for 0, 1, 2, 3, 4 and 5 days with gravimetric methode and determined by Friedman test; comparison of glucose content for each product determined by Anova because its distribution are normal and its variation are homogen, or by Kruskal-Wallis because its distribution are unnormal and its variation are unhomogen using SPSS version 15.0 with level of statistic confidence 99%. The result showed that the storage duration was influenced toward glucose content of fresh milk, full cream milk powder solution and sweet concentrate milk solution significantly and there are significance difference of glucose content for each products with the manipulation on storage duration.Key words : storage duration, glucose, fresh milk, full cream milk powder solution and sweet concentrate milk solution